SISTEM INFORMASI ABSENSI MENGGUNAKAN TEKNOLOGI RFID DI CV MULTI KARYA MITRA BERBASIS WEB - ROPIKA AYU YOLANDA; Darmansah (Computer Science and Industrial Engineering, 2024)
In previous research that the author conducted on practical work implementation, the author created a system that can carry out attendance using Radio-Frequency Identification (RFID) which will read each RFID Identification (ID) or Unique Identifier (UID) owned by each employee. The UID has previously been stored in the program so that it can be detected when it is registered. However, this system has a few shortcomings, namely that it has not been integrated with each other between the main office and branch offices, so the existing systems still stand alone. Apart from that, the monthly absenteeism recapitulation process is also not optimal because it cannot automatically calculate the number of attendances for each employee. Given the problems above, the author developed a system that had previously been created by integrating the two attendance devices with a Web-based database system so that the attendance data for each employee would be directly stored in the database. This data will later be used to facilitate monthly recapitulation for each employee. By integrating the device with a database, the storage carried is not easily lost, so it can be used at another time